2015
DOI: 10.1902/jop.2015.140678
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Therapy Effects on Nitrite Related to Oral Bacteria: A 6‐Month Randomized Clinical Trial

Abstract: The relationship between nitrite and bacterial levels appears weak. Short-term scaling exhibited a greater influence on nitrite concentrations then long-term CHX use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…However, the way in which the mechanical procedures are performed seems to influence the results. The studies conducted by our group revealed a decrease in the salivary arginase activity (SAA) after quadrant-wise scaling 11,12 , despite a tendency toward a salivary nitrite increase (also related to the NO cycle) after full-mouth scaling 6 . Mechanical procedures can also be combined with chemical agents for the treatment of gingivitis and periodontitis.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the way in which the mechanical procedures are performed seems to influence the results. The studies conducted by our group revealed a decrease in the salivary arginase activity (SAA) after quadrant-wise scaling 11,12 , despite a tendency toward a salivary nitrite increase (also related to the NO cycle) after full-mouth scaling 6 . Mechanical procedures can also be combined with chemical agents for the treatment of gingivitis and periodontitis.…”
Section: Introductionmentioning
confidence: 87%
“…The increased salivary arginase levels 5 observed in the course of periodontal disease and their subsequent reduction after treatment 6 suggest the involvement of arginase in the inflammatory process. Castro Arginase is an enzyme that catalyzes the hydrolysis of L-arginine into L-ornithine and urea, and it can be found in mammalian tissues in two isoforms: type-I arginase (Arg-I), which is present in the cytosol and a critical hepatic metabolism enzyme, and type-II arginase (Arg-II), which is located in the mitochondria of extrahepatic tissues and modulates the L-arginine levels for the synthesis of nitric oxide (NO), polyamines, and proteins 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the likelihood of P.intermedia being detected in saliva is 13 times higher for smokers than for non-smokers. There have been several studies that have shown that the risk of periodontal disease is 1.63 times higher [19], and the risk of periodontitis is 2.5-6 times higher [20]. The likelihood of periodontitis incidence and deterioration is 5-7 times higher in heavy smokers [21].…”
Section: Discussionmentioning
confidence: 99%
“…Samples of saliva 6 and from the dorsum of the tongue 5 were collected from the total population (n=154). Saliva samples were collected in the morning, between 8:00 and 11:00.…”
Section: Methodsmentioning
confidence: 99%